The paradox of silence in the sirens’ song - Carreño, Paz (Re-presentaciones: Periodismo, comunicación y sociedad, 2023)
The Odyssey is an epic poem that recounts Odysseus’ voyage to the Trojan War and back home. Tragedy appears in the story at more than one point. In this essay I seek to think about the moment when Odysseus finds himself in front of the sirens, as this scene opens a paradox around the experience of silence: can silence be heard? I will address from four notes how the experience of silence becomes tragic, insofar as it makes its representation impossible. In such a context, I seek to strain Ulysses’ passage through the island and his triumph over the sirens in order to open up other horizons of listening.